Crystallization and preliminary X‐ray diffraction analysis of YhbJ from Escherichia coli, a key protein involved in the GlmYZ sRNA regulatory cascade. Issue 2 (5th February 2013) - Resch, Marcus; Göpel, Yvonne; Görke, Boris; Ficner, Ralf
<x xml:space="preserve">Abstract</x> The protein YhbJ from Escherichia coli was previously reported to be involved in the regulation of glucosamine‐6‐phosphate synthase (GlmS) synthesis. YhbJ controls a regulatory cascade composed of the two small RNAs GlmY and GlmZ, which in turn regulate GlmS synthesis. For structural characterization, YhbJ was cloned, expressed and purified to homogeneity by Strep‐tag affinity chromatography and size‐exclusion chromatography. Multi‐angle laser light‐scattering analysis revealed its homotrimeric state in solution. The protein crystallized in two distinct trigonal crystal forms, with unit‐cell parameters a = b = 91.62, c = 352.82 Å for space group P321 and a = b = 92.72, c = 156.75 Å for one of the enantiomorphic space groups P31 or P32. Preliminary analysis of the diffraction data suggests the presence of approximately three to seven molecules per asymmetric unit. Owing to the lack of a suitable homologous model, structure determination by means of MIR and MAD methods is required.